Steinernema goweni n. sp. (Rhabditida: Steinernematidae), a new entomopathogenic nematode from Zulia State, Venezuela - San-Blas, Ernesto; Morales-Montero, Patricia; Portillo, Edgar; Nermuť, Jiří; Puza, Vladimir (Zootaxa, 2016)
A nematode from the genus Steinernema was isolated in Zulia state (North-western, Venezuela). Morphological, morphometric and molecular studies indicated that this nematode belongs to the “bicornutum” group and is described herein as Steinernema goweni n. sp. Steinernema goweni n. sp. is characterised by morphometrics of its infective juveniles, with body length 640 (531–719) µm, pharynx length of 119 (109–126) µm, tail of 67 (59–89) µm, c ratio = 9 (6–11) and E% = 77 (48–94). First generation male specimens can be recognised by the shape and size of spicules (55 (50–57) µm long) and gubernaculum (35 (30–40) µm long), and %D value 42 (28–59), which is at the lower limit within the “bicornutum” group. The number of genital papillae in males is also distinctive for S. goweni n. sp. presenting up to 27 (13 pairs + 1) papillae in 15% of specimens. The phasmids can be seen in scanning electron microscopy in all stages, characters not previously reported within the “bicornutum” group. Phylogenetic analyses of the “bicornutum” group based on both ITS and D2D3 regions showed a clear separation of S. goweni n. sp. from the other species. In both analyses S. goweni n. sp. formed a strongly supported group of American species.